Community structures of total bacterial DNA, cultivable bacteria and prototrophs in bulk soil and rhizospheres - Neelawan Pongsilp (2018)
Aims: It has been hypothesized that root exudates can be a nutritional factor influencing the bacterial community structure as well as the occurrence of prototrophs and auxotrophs in rhizospheres. The present study was performed to examine the community structures of total bacterial DNA, cultivable bacteria and prototrophs in 3 soil samples with different levels of abundance of root exudates. Methodology and results: Denaturing gradient gel electrophoresis (DGGE) was performed to examine the community structures of total bacterial DNA, cultivable bacteria and prototrophs in 3 soil samples including bulk soil, rhizosphere of a single plant species and rhizosphere of multiple plant species. For clustering analysis, a dendrogram generated from the DGGE patterns revealed the different bacterial community structures in these soil samples. Both rhizospheres claded together, separating from bulk soil. The DGGE patterns of cultivable bacteria showed particular fingerprints corresponding to kinds of media and soil samples. Nutrient agar (NA) medium, isolation medium for prototroph (IMP) and IMP supplemented with soil extracts were used for bacterial cultivations. Prototrophs were isolated and examined by random amplified polymorphic DNA (RAPD) and 16S rRNA gene sequence analysis. The genetic diversity of prototrophs in 3 soil samples was similar (approximately 5% to 10% similarities) and most of them (13 of 28 strains) were members of Pseudomonas with 97% to 100% identities. Conclusion, significance, and impact of study: The present study provides a strong evidence of the influence of root exudates and plant species on bacterial community structures.